Zwalczanie kultu obrazów w dobie reformacji - Maria Gołda-Sobczak (Czasopismo Prawno-Historyczne)
The rejection and destruction of images, which was so characteristic of the iconoclastic movement of Eastern Christianity, was revived in the Reformation period. The theoretical foundation for this movement was provided by Erasmus of Rotterdam and it was later fully developed by Martin Luther, John Calvin and their successors. This movement had its origins in theology but also there were social and even national roots (in the Netherlands). The position developed during the Reformation period seems to have made an impression on the reception of works of art by the contemporaries not only in Protestant circles but in Catholic ones as well.